Avatar, the last airbender. The promise, part one - Yang, Gene Luen (Avatar, the last airbender (Graphic novel series), 2012)
Picking up exactly where Avatar: The Last Airbender left off, The Promise takes Aang to a Fire Nation colony in the heart of the Earth Nation, where tensions between neighbors threaten to shatter the world's newfound peace-putting the Avatar on a collision course with one of his closest friends, FireLord Zuko.